Analisis VRIO dan PEST pada Strategi Bisnis KSPPS Hanada Quwais Sembada - Azzahra Prania Putri; Muhammad Bagas Adi Nugroho; Nisrina Alifatu Zahra; Yoiz Shofwa Shafrani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to evaluate the approach in assessing resources and business environment in KSPPS Hanada Quwais Sembada using VRIO (Value, Rare, Imitability, Organization) and PEST (Politic, Economic, Social, Technology) frameworks. The VRIO framework is applied to find internal and sustainable competitive advantages by analyzing the company's resources and capabilities. On the other hand, PEST analysis is conducted to explore external macro factors that have the potential to affect the institution's performance and strategy. Through a case study on KSPPS Hanada Quwais Sembada KC Purwokerto, it is seen that this institution has several valuable resources, such as a high level of member trust and a unique sharia-based business model, but needs to improve the aspects of rarity and capabilities that are difficult to imitate. From the outside, changes in Islamic banking regulations and the adoption of digital technology by members are identified as significant opportunities and challenges.